The infectivity and lytic activity of minute virus of mice wild-type and derived vector particles are strikingly different - Lang, Susanne; Rommelaere, Jean; Dinsart, Christiane (Journal of virology, 2005)
Gene therapy vectors have been developed from autonomous rodent parvoviruses that carry a therapeutic gene or a marker gene in place of the genes encoding the capsid proteins. These vectors are currently evaluated in preclinical experiments. The infectivity of the vector particles deriving from the fibroblastic strain of minute virus of mice (MVMp) (produced by transfection in human cells) was found to be far less (approximately 50-fold-less) infectious than that of wild-type virus particles routinely produced by infection of A9 mouse fibroblasts. Similarly, wild-type MVMp produced by transfection also had a low infectivity in mouse cells, indicating that the method and producer cells influence the infectivity of the virus produced. Interestingly, producer cells made as many full vector particles as wild-type particles, arguing against deficient packaging being responsible for the low infectivity of viruses recovered from transfected cells. The hurdle to infection with full particles produced through transfection was found to take place at an early step following entry and limiting viral DNA replication and gene expression. Infections with transfection or infection-derived virus stocks normalized for their replication ability yielded similar monomer and dimer DNA amplification and gene expression levels. Surprisingly, at equivalent replication units, the capacity of parvovirus vectors to kill tumor cells was lower than that of the parental wild-type virus produced under the same transfection conditions, suggesting that beside the viral nonstructural proteins, the capsid proteins, assembled capsids, or the corresponding coding region contribute to the lytic activity of these viruses.
Published online December 13, 2004
Gesehen am 19.02.2021